Modified silica / polyimide separation membrane, and preparation method and application thereof
Patent Information
- Application Number
- CN202410406856.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-07
AI Technical Summary
[0005]本发明的目的在于提供一种改性二氧化硅/聚酰亚胺分离膜及其制备方法和应用,解决现有技术制备的二氧化硅气体分离膜气体渗透分离作用差和水汽稳定性差的问题
[0023](1)本发明首先将负载金属氧化物前驱体的氧化石墨烯(GO)与二胺单体进行反应,GO表面的含氧官能团与二胺单体通过化学键结合,提高了GO在聚酰亚胺膜上的分散性以及牢固性;然后加入二酐单体进行缩聚反应生成聚酰胺酸溶液,再加入二氧化硅溶胶,进行涂膜干燥后煅烧,一方面形成自支撑的二氧化硅/聚酰亚胺(SiO2/PI)复合基质膜,另一方面金属氧化物前驱体分解形成金属氧化物,最终得到GO和金属氧化物改性的SiO2/PI分离膜。
Abstract
Description
Technical Field
[0001] This invention relates to the field of gas separation membrane technology, and in particular to a modified silica / polyimide separation membrane, its preparation method, and its application. Background Technology
[0002] Carbon dioxide is a significant pollutant in natural gas, causing various industrial problems such as acid formation upon contact with water leading to pipeline corrosion, natural gas hydrate formation, and reduced natural gas transport capacity and calorific value. It is also a major greenhouse gas, primarily produced by flue gas from coal-fired plants, thus impacting global climate. With the increasingly severe global climate change situation, research into technologies to reduce greenhouse gas emissions has become a hot topic. Intensive research has been conducted to capture carbon dioxide from gases such as natural gas, biogas, and flue gas. However, most carbon dioxide capture technologies suffer from drawbacks such as high operating costs, large scale, and high energy consumption. This has continuously spurred research into high-performance, lower-cost, and green gas separation technologies.
[0003] Conventional carbon dioxide capture technologies include adsorption, absorption, cryogenic methods, and membrane separation. Among these methods, membrane separation is widely used in various gas separation processes due to its advantages such as low cost, small footprint, low energy consumption, simple operation, and no environmental pollution. Silica membranes, as a type of inorganic ceramic membrane, possess advantages such as chemical stability, easy regeneration, and easy control of pore size and distribution, making them a good choice for gas separation membrane materials. However, in actual gas separation processes, silica membranes exhibit limited gas permeation separation and poor water vapor stability, failing to meet industrial requirements.
[0004] Therefore, developing a gas separation membrane with high CO2 gas separation selectivity and permeability is an urgent problem to be solved. Summary of the Invention
[0005] The purpose of this invention is to provide a modified silica / polyimide separation membrane, its preparation method, and its application, thereby solving the problems of poor gas permeation separation and poor water vapor stability of silica gas separation membranes prepared by existing technologies.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0007] This invention provides a method for preparing a modified silica / polyimide separation membrane, comprising the following steps:
[0008] (1) Graphene oxide, metal oxide precursor and anhydrous ethanol are mixed and rotary evaporated to obtain graphene oxide-metal oxide precursor composite powder.
[0009] (2) After mixing graphene oxide-metal oxide precursor composite powder, diamine monomer and solvent and reacting, dianhydride monomer is added to carry out polycondensation reaction to obtain modified polyamic acid solution.
[0010] (3) Mix the silica sol with the modified polyamic acid solution to obtain a mixture;
[0011] The mixture is coated onto a substrate and dried to obtain a composite film;
[0012] The composite membrane was calcined under a protective atmosphere to obtain a modified silica / polyimide separation membrane.
[0013] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the ratio of graphene oxide, metal oxide precursor, and anhydrous ethanol in step (1) is 1-3 g: 1-1.5 mol: 0.5-1 L; the metal oxide precursor is one or more of zinc nitrate, magnesium nitrate, copper nitrate, iron nitrate, nickel nitrate, aluminum nitrate, and cerium nitrate; and the rotary evaporation temperature is 70-90 °C.
[0014] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the ratio of the amount of graphene oxide-metal oxide precursor composite powder, diamine monomer, dianhydride monomer, and solvent in step (2) is 1-8 g: 0.1-1 mol: 0.1-0.5 mol: 200-300 mL.
[0015] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the diamine monomer in step (2) is 4,4'-diaminobenzoylaniline; the dianhydride monomer is one or more of 4,4'-(hexafluoroisopropene) phthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclopentanetetracarboxylic anhydride, and 1,2,3,4-cyclobutanetetracarboxylic anhydride.
[0016] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the reaction temperature in step (2) is 40-60°C; the reaction time is 4-8 h; the polycondensation reaction temperature is 20-30°C; and the polycondensation reaction time is 2-5 h.
[0017] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the method for preparing the silica sol in step (3) is as follows: a silicon source, anhydrous ethanol, and water are mixed, and then an acidic catalyst is added to react and obtain silica sol.
[0018] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the volume ratio of silica sol and modified polyamic acid solution in step (3) is 1-5:3-10.
[0019] Preferably, in the above-mentioned method for preparing a modified silica / polyimide separation membrane, the calcination conditions in step (3) are as follows: first, the temperature is raised to 200-250°C at a rate of 0.5-2°C / min and held for 0.5-1.5h, and then the temperature is raised to 350-450°C at a rate of 1-5°C / min and held for 1-3h.
[0020] The present invention also provides a method for preparing a modified silica / polyimide separation membrane to obtain a modified silica / polyimide separation membrane.
[0021] The present invention also provides an application of a modified silica / polyimide separation membrane in carbon dioxide separation.
[0022] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) In this invention, graphene oxide (GO) loaded with metal oxide precursor is first reacted with diamine monomer. The oxygen-containing functional groups on the surface of GO are chemically bonded to the diamine monomer, which improves the dispersibility and firmness of GO on the polyimide film. Then, dianhydride monomer is added to carry out a polycondensation reaction to generate a polyamic acid solution. Then, silica sol is added, and the film is coated, dried and calcined. On the one hand, a self-supporting silica / polyimide (SiO2 / PI) composite matrix film is formed. On the other hand, the metal oxide precursor is decomposed to form metal oxide. Finally, GO and metal oxide modified SiO2 / PI separation film are obtained.
[0024] (2) This invention combines the advantages of SiO2 membrane and PI membrane. By controlling the synthesis of PI from specific diamine and dianhydride monomers, the hydroxyl groups on the surface of SiO2 are linked to the amide groups in the PI structure by hydrogen bonds, which enhances the binding of the composite membrane. The resulting composite matrix membrane has a controllable pore structure, stable chemical properties, and good gas permeability. On this basis, it is further modified with graphene oxide and metal oxide. The high specific surface area, high mechanical strength, and high water vapor stability of graphene oxide can enhance the separation of CO2 and improve the water vapor stability of the separation membrane. The modification of metal oxide makes the separation membrane have a strong affinity for CO2, which can promote CO2 transfer and improve separation selectivity.
[0025] (3) The preparation method of the present invention is simple, easy to operate, and has controllable conditions, making it suitable for large-scale production. Detailed Implementation
[0026] This invention provides a method for preparing a modified silica / polyimide separation membrane, comprising the following steps:
[0027] (1) Graphene oxide, metal oxide precursor and anhydrous ethanol are mixed and rotary evaporated to obtain graphene oxide-metal oxide precursor composite powder.
[0028] (2) After mixing graphene oxide-metal oxide precursor composite powder, diamine monomer and solvent and reacting, dianhydride monomer is added to carry out polycondensation reaction to obtain modified polyamic acid solution.
[0029] (3) Mix the silica sol with the modified polyamic acid solution to obtain a mixture;
[0030] The mixture is coated onto a substrate and dried to obtain a composite film;
[0031] The composite membrane was calcined under a protective atmosphere to obtain a modified silica / polyimide separation membrane.
[0032] In this invention, the preferred ratio of graphene oxide, metal oxide precursor, and anhydrous ethanol in step (1) is 1-3g: 1-1.5mol: 0.5-1L, more preferably 2-3g: 1.1-1.5mol: 0.7-1L, and even more preferably 3g: 1.2mol: 1L.
[0033] In this invention, the metal oxide precursor in step (1) is preferably one or more of zinc nitrate, magnesium nitrate, copper nitrate, iron nitrate, nickel nitrate, aluminum nitrate, and cerium nitrate, more preferably one or more of zinc nitrate, magnesium nitrate, copper nitrate, and iron nitrate, and more preferably magnesium nitrate.
[0034] In this invention, the temperature of rotary evaporation in step (1) is preferably 70-90°C, more preferably 75-90°C, and even more preferably 80°C.
[0035] In this invention, the preferred ratio of the graphene oxide-metal oxide precursor composite powder, diamine monomer, dianhydride monomer, and solvent in step (2) is 1-8g: 0.1-1mol: 0.1-0.5mol: 200-300mL, more preferably 3-8g: 0.5-1mol: 0.1-0.4mol: 230-270mL, and even more preferably 6g: 0.7mol: 0.3mol: 250mL.
[0036] In this invention, the diamine monomer in step (2) is preferably 4,4'-diaminobenzoyl aniline.
[0037] In this invention, the dianhydride monomer in step (2) is preferably one or more of 4,4'-(hexafluoroisopropene) phthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclopentanetetracarboxylic anhydride, and 1,2,3,4-cyclobutanetetracarboxylic anhydride, more preferably one or more of 3,3',4,4'-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclopentanetetracarboxylic anhydride, and 1,2,3,4-cyclobutanetetracarboxylic anhydride, and more preferably 1,2,3,4-cyclopentanetetracarboxylic anhydride.
[0038] In this invention, the solvent in step (2) is preferably N,N-dimethylacetamide or N-methylpyrrolidone, and more preferably N,N-dimethylacetamide.
[0039] In this invention, the temperature of the reaction in step (2) is preferably 40-60°C, more preferably 45-60°C, and even more preferably 50°C; the reaction time is preferably 4-8h, more preferably 4-6h, and even more preferably 5h.
[0040] In this invention, the temperature of the polycondensation reaction in step (2) is preferably 20-30°C, more preferably 23-28°C, and even more preferably 25°C; the time of the polycondensation reaction is preferably 2-5 hours, more preferably 3-5 hours, and even more preferably 4 hours.
[0041] In this invention, the preparation method of the silica sol in step (3) is as follows: a silicon source, anhydrous ethanol and water are mixed, and then an acidic catalyst is added to react and obtain silica sol.
[0042] In this invention, in the method for preparing silica sol in step (3), the silica source is preferably a mixture of tetraethyl orthosilicate and 3-aminopropyltriethoxysilane, more preferably a mixture of tetraethyl orthosilicate and 3-aminopropyltriethoxysilane in a mass ratio of 5-8:1-3, and even more preferably a mixture of tetraethyl orthosilicate and 3-aminopropyltriethoxysilane in a mass ratio of 7:3.
[0043] In this invention, in the method for preparing silica sol in step (3), the acidic catalyst is preferably one or more of hydrochloric acid, nitric acid, acetic acid, and sulfuric acid, more preferably one or more of hydrochloric acid, nitric acid, and acetic acid, and even more preferably hydrochloric acid; the concentration of the acidic catalyst is preferably 3 to 6 mol / L, more preferably 4 to 6 mol / L, and even more preferably 5 mol / L.
[0044] In this invention, in the method for preparing silica sol in step (3), the molar ratio of the silicon source, anhydrous ethanol, water, and acidic catalyst is preferably 1:4-6:5-8:0.05-0.2, more preferably 1:5-6:7-8:0.07-0.15, and even more preferably 1:5:7:0.1.
[0045] In this invention, in the method for preparing silica sol in step (3), the reaction temperature is preferably 70-80°C, more preferably 75-80°C, and even more preferably 80°C; the reaction time is preferably 2-5 hours, more preferably 2-4 hours, and even more preferably 3 hours.
[0046] In this invention, the volume ratio of silica sol and modified polyamic acid solution in step (3) is preferably 1-5:3-10, more preferably 3-5:5-10, and even more preferably 4:9.
[0047] In this invention, the substrate in step (3) is preferably a glass plate.
[0048] In this invention, the drying temperature in step (3) is preferably 100-120°C, more preferably 110-120°C, and even more preferably 120°C; the drying time is preferably 8-16 hours, more preferably 10-15 hours, and even more preferably 12 hours.
[0049] In this invention, the coating in step (3) can be performed using methods well known to those skilled in the art.
[0050] In this invention, the preferred calcination conditions in step (3) are: first, heating to 200-250°C at a rate of 0.5-2°C / min and holding for 0.5-1.5h, then heating to 350-450°C at a rate of 1-5°C / min and holding for 1-3h; more preferably, heating to 220-250°C at a rate of 0.5-1°C / min and holding for 0.5-1h, then heating to 370-450°C at a rate of 1-3°C / min and holding for 2-3h; even more preferably, heating to 230°C at a rate of 0.5°C / min and holding for 0.5h, then heating to 420°C at a rate of 1°C / min and holding for 2h.
[0051] In this invention, the protective atmosphere in step (3) is preferably nitrogen.
[0052] In this invention, the thickness of the modified silica / polyimide separation membrane in step (3) is preferably 50-100 μm. It is better to have a thinner separation membrane while ensuring that the separation membrane is free of defects.
[0053] The present invention also provides a method for preparing a modified silica / polyimide separation membrane to obtain a modified silica / polyimide separation membrane.
[0054] The present invention also provides an application of a modified silica / polyimide separation membrane in carbon dioxide separation.
[0055] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0056] Example 1
[0057] This embodiment provides a modified silica / polyimide separation membrane, the preparation method of which includes the following steps:
[0058] (1) Graphene oxide, metal oxide precursor (ferric nitrate) and anhydrous ethanol are mixed evenly at a ratio of 3g:1mol:1L, and then the anhydrous ethanol is removed by rotary evaporation at 80℃ to obtain graphene oxide-metal oxide precursor composite powder.
[0059] (2) After uniformly mixing the graphene oxide-metal oxide precursor composite powder, the diamine monomer (4,4'-diaminobenzoyl aniline), and N,N-dimethylacetamide, the mixture was heated to 60℃ and reacted for 5 hours. Then, the mixture was cooled to 25℃, and the dianhydride monomer (3,3',4,4'-biphenyltetracarboxylic acid dianhydride) was added to carry out a polycondensation reaction for 3 hours to obtain a modified polyamic acid solution. The ratio of the graphene oxide-metal oxide precursor composite powder, the diamine monomer, the dianhydride monomer, and N,N-dimethylacetamide was 6 g: 0.8 mol: 0.5 mol: 250 mL.
[0060] (3) Mix silicon source (tetraethyl orthosilicate and 3-aminopropyltriethoxysilane in a mass ratio of 7:3), anhydrous ethanol and water evenly, then add 5 mol / L hydrochloric acid, heat to 80℃ and react for 3 h to obtain silica sol; wherein the molar ratio of silicon source, anhydrous ethanol, water and hydrochloric acid is 1:5:7:0.09.
[0061] (4) The silica sol and the modified polyamic acid solution were stirred and mixed evenly at a volume ratio of 4:9 to obtain a mixture; the mixture was coated on a glass plate and dried at 120℃ for 10h before being removed from the glass plate to obtain a composite film;
[0062] (5) The composite membrane was heated from room temperature to 220℃ at a rate of 0.5℃ / min and held for 0.5h under a nitrogen atmosphere, and then heated to 400℃ at a rate of 2℃ / min and held for 1h. The temperature was then lowered to room temperature to obtain a modified silica / polyimide separation membrane with a thickness of 80μm.
[0063] The separation membrane prepared above was subjected to permeation performance testing under the conditions of 50℃ and 0.35MPa. The permeation coefficient of the separation membrane for CO2 was 196.4 Barrer; after working in a water vapor environment for 168 hours, the permeation coefficient for CO2 was 192.3 Barrer.
[0064] The separation membranes prepared above were tested for separation factors containing carbon dioxide gas (CO2 / N2, CO2 / O2) under the conditions of 50℃ and 0.35MPa. The CO2 / N2 separation factor of the above separation membranes was 38.43, and the CO2 / O2 separation factor was 35.06; after working in a water vapor environment for 168 hours, the CO2 / N2 separation factor was 37.00, and the CO2 / O2 separation factor was 32.80.
[0065] Example 2
[0066] This embodiment provides a modified silica / polyimide separation membrane, the preparation method of which includes the following steps:
[0067] (1) Graphene oxide, metal oxide precursor (copper nitrate) and anhydrous ethanol were mixed evenly at a ratio of 1g:1.1mol:0.8L, and then the anhydrous ethanol was removed by rotary evaporation at 70℃ to obtain graphene oxide-metal oxide precursor composite powder.
[0068] (2) After uniformly mixing the graphene oxide-metal oxide precursor composite powder, the diamine monomer (4,4'-diaminobenzoyl aniline), and N,N-dimethylacetamide, the mixture was heated to 50℃ and reacted for 4 hours. Then, the mixture was cooled to 25℃, and the dianhydride monomer (4,4'-(hexafluoroisopropene) phthalic anhydride) was added to carry out a polycondensation reaction for 4 hours to obtain a modified polyamic acid solution. The ratio of the graphene oxide-metal oxide precursor composite powder, the diamine monomer, the dianhydride monomer, and N,N-dimethylacetamide was 3g:0.6mol:0.2mol:200mL.
[0069] (3) Mix silicon source (tetraethyl orthosilicate and 3-aminopropyltriethoxysilane in a mass ratio of 7:3), anhydrous ethanol and water evenly, then add 4 mol / L nitric acid, heat to 70℃ and react for 3 h to obtain silica sol; wherein the molar ratio of silicon source, anhydrous ethanol, water and nitric acid is 1:4:7:0.1;
[0070] (4) The silica sol and the modified polyamic acid solution were stirred and mixed evenly at a volume ratio of 2:7 to obtain a mixture; the mixture was coated on a glass plate and dried at 120°C for 8 hours before being removed from the glass plate to obtain a composite film;
[0071] (5) The composite membrane was heated from room temperature to 210℃ at a rate of 0.8℃ / min and held for 0.5h under a nitrogen atmosphere, and then heated to 380℃ at a rate of 1℃ / min and held for 2h. The temperature was then lowered to room temperature to obtain a modified silica / polyimide separation membrane with a thickness of 82μm.
[0072] The separation membrane prepared above was subjected to permeation performance testing under the conditions of 50℃ and 0.35MPa. The permeation coefficient of the separation membrane for CO2 was 167.72 Barrer; after working in a water vapor environment for 168 hours, the permeation coefficient for CO2 was 162.65 Barrer.
[0073] The separation membranes prepared above were tested for separation factors containing carbon dioxide gas (CO2 / N2, CO2 / O2) under the conditions of 50℃ and 0.35MPa. The CO2 / N2 separation factor of the above separation membranes was 34.56, and the CO2 / O2 separation factor was 32.46; after working in a water vapor environment for 168 hours, the CO2 / N2 separation factor was 32.72, and the CO2 / O2 separation factor was 30.53.
[0074] Example 3
[0075] This embodiment provides a modified silica / polyimide separation membrane, the preparation method of which includes the following steps:
[0076] (1) Graphene oxide, metal oxide precursor (magnesium nitrate) and anhydrous ethanol were mixed evenly at a ratio of 3g:1.5mol:1L, and then the anhydrous ethanol was removed by rotary evaporation at 90℃ to obtain graphene oxide-metal oxide precursor composite powder.
[0077] (2) After uniformly mixing the graphene oxide-metal oxide precursor composite powder, the diamine monomer (4,4'-diaminobenzoyl aniline), and N,N-dimethylacetamide, the mixture was heated to 60℃ and reacted for 4 hours. Then, the mixture was cooled to 25℃, and the dianhydride monomer (1,2,3,4-cyclopentanetetracarboxylic acid dianhydride) was added to carry out a polycondensation reaction for 5 hours to obtain a modified polyamic acid solution. The ratio of the graphene oxide-metal oxide precursor composite powder, the diamine monomer, the dianhydride monomer, and N,N-dimethylacetamide was 5 g: 0.7 mol: 0.5 mol: 300 mL.
[0078] (3) Mix silicon source (tetraethyl orthosilicate and 3-aminopropyltriethoxysilane in a mass ratio of 7:3), anhydrous ethanol and water evenly, then add 5 mol / L acetic acid, heat to 75℃ and react for 4 h to obtain silica sol; wherein the molar ratio of silicon source, anhydrous ethanol, water and acetic acid is 1:6:5:0.2.
[0079] (4) The silica sol and the modified polyamic acid solution were stirred and mixed evenly at a volume ratio of 5:6 to obtain a mixture; the mixture was coated on a glass plate and dried at 120℃ for 12h before being removed from the glass plate to obtain a composite film;
[0080] (5) The composite membrane was heated from room temperature to 240℃ at a rate of 1℃ / min and held for 1h under a nitrogen atmosphere, and then heated to 430℃ at a rate of 3℃ / min and held for 2h. The temperature was then lowered to room temperature to obtain a modified silica / polyimide separation membrane with a thickness of 85μm.
[0081] The separation membrane prepared above was subjected to permeation performance testing under the conditions of 50℃ and 0.35MPa. The permeability coefficient of the separation membrane for CO2 was 209.2 Barrer; after working in a water vapor environment for 168 hours, the permeability coefficient for CO2 was 205.4 Barrer.
[0082] The separation membranes prepared above were tested for separation factors containing carbon dioxide gas (CO2 / N2, CO2 / O2) under the conditions of 50℃ and 0.35MPa. The CO2 / N2 separation factor of the above separation membranes was 36.55, and the CO2 / O2 separation factor was 33.69; after working in a water vapor environment for 168 hours, the CO2 / N2 separation factor was 35.10, and the CO2 / O2 separation factor was 31.70.
[0083] Example 4
[0084] This embodiment provides a modified silica / polyimide separation membrane, the preparation method of which includes the following steps:
[0085] (1) Graphene oxide, metal oxide precursor (zinc nitrate) and anhydrous ethanol were mixed evenly at a ratio of 2g:1.3mol:0.8L, and then the anhydrous ethanol was removed by rotary evaporation at 70℃ to obtain graphene oxide-metal oxide precursor composite powder.
[0086] (2) After uniformly mixing the graphene oxide-metal oxide precursor composite powder, the diamine monomer (4,4'-diaminobenzoyl aniline), and N-methylpyrrolidone, the mixture was heated to 50°C and reacted for 7 hours. Then, the mixture was cooled to 25°C, and the dianhydride monomer (1,2,3,4-cyclobutanetetracarboxylic acid dianhydride) was added to carry out a polycondensation reaction for 2 hours to obtain a modified polyamic acid solution. The ratio of the graphene oxide-metal oxide precursor composite powder, the diamine monomer, the dianhydride monomer, and N-methylpyrrolidone was 8 g: 0.6 mol: 0.2 mol: 250 mL.
[0087] (3) Mix silicon source (tetraethyl orthosilicate and 3-aminopropyltriethoxysilane in a mass ratio of 7:3), anhydrous ethanol and water evenly, then add 4 mol / L hydrochloric acid, heat to 80℃ and react for 2 h to obtain silica sol; wherein the molar ratio of silicon source, anhydrous ethanol, water and hydrochloric acid is 1:4:8:0.1;
[0088] (4) The silica sol and the modified polyamic acid solution were stirred and mixed evenly at a volume ratio of 2:9 to obtain a mixture; the mixture was coated on a glass plate and dried at 120℃ for 16 hours before being removed from the glass plate to obtain a composite film;
[0089] (5) The composite membrane was heated from room temperature to 250℃ at a rate of 2℃ / min and held for 1.5h under a nitrogen atmosphere, and then heated to 450℃ at a rate of 1℃ / min and held for 2h. The membrane was then cooled to room temperature to obtain a modified silica / polyimide separation membrane with a thickness of 81μm.
[0090] The separation membrane prepared above was subjected to permeation performance testing under the conditions of 50℃ and 0.35MPa. The permeation coefficient of the separation membrane for CO2 was 188.5 Barrer; after working in a water vapor environment for 168 hours, the permeation coefficient for CO2 was 184.2 Barrer.
[0091] The separation membranes prepared above were tested for separation factors containing carbon dioxide gas (CO2 / N2, CO2 / O2) under the conditions of 50℃ and 0.35MPa. The CO2 / N2 separation factor of the above separation membranes was 29.82, and the CO2 / O2 separation factor was 31.03; after working in a water vapor environment for 168 hours, the CO2 / N2 separation factor was 27.84, and the CO2 / O2 separation factor was 28.95.
[0092] Comparative Example 1
[0093] This comparative example provides a silica / polyimide separation membrane, specifically as described in Example 1, except that step (1) is omitted and graphene oxide-metal oxide precursor composite powder is not added in step (2).
[0094] The separation membrane prepared above was subjected to permeation performance testing under the conditions of 50℃ and 0.35MPa. The permeation coefficient of the separation membrane for CO2 was 88.7 Barrer; after working in a water vapor environment for 168 hours, the permeation coefficient for CO2 was 61.4 Barrer.
[0095] The separation membranes prepared above were tested for separation factors containing carbon dioxide gas (CO2 / N2, CO2 / O2) under the conditions of 50℃ and 0.35MPa. The CO2 / N2 separation factor of the above separation membranes was 12.63, and the CO2 / O2 separation factor was 14.58; after working in a water vapor environment for 168 hours, the CO2 / N2 separation factor was 7.29, and the CO2 / O2 separation factor was 10.37.
[0096] Comparative Example 2
[0097] This comparative example provides a modified silica / polyimide separation membrane, specifically as described in Example 1, except that no metal oxide precursor is added in step (1), and only graphene oxide is used.
[0098] The separation membrane prepared above was subjected to permeation performance testing under the conditions of 50℃ and 0.35MPa. The permeation coefficient of the above separation membrane for CO2 was 133.10 Barrer; after working in a water vapor environment for 168 hours, the permeation coefficient for CO2 was 121.86 Barrer.
[0099] The separation membranes prepared above were tested for separation factors containing carbon dioxide gas (CO2 / N2, CO2 / O2) under the conditions of 50℃ and 0.35MPa. The CO2 / N2 separation factor of the above separation membranes was 21.59, and the CO2 / O2 separation factor was 24.65; after working in a water vapor environment for 168 hours, the CO2 / N2 separation factor was 18.92, and the CO2 / O2 separation factor was 20.86.
[0100] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified silica / polyimide separation membrane, characterized in that, Includes the following steps: (1) Graphene oxide, metal oxide precursor and anhydrous ethanol are mixed and rotary evaporated to obtain graphene oxide-metal oxide precursor composite powder. (2) After mixing graphene oxide-metal oxide precursor composite powder, diamine monomer and solvent and reacting, dianhydride monomer is added to carry out polycondensation reaction to obtain modified polyamic acid solution. (3) Mix the silica sol with the modified polyamic acid solution to obtain a mixture; The mixture is coated onto a substrate and dried to obtain a composite film; The composite membrane was calcined under a protective atmosphere to obtain a modified silica / polyimide separation membrane; In step (1), the ratio of graphene oxide, metal oxide precursor, and anhydrous ethanol is 1~3 g: 1~1.5 mol: 0.5~1 L; the metal oxide precursor is one or more of zinc nitrate, magnesium nitrate, copper nitrate, iron nitrate, nickel nitrate, aluminum nitrate, and cerium nitrate; the rotary evaporation temperature is 70~90 ℃. The diamine monomer in step (2) is 4,4'-diaminobenzoylaniline; the dianhydride monomer is one or more of 4,4'-(hexafluoroisopropene) phthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclopentanetetracarboxylic anhydride, and 1,2,3,4-cyclobutanetetracarboxylic anhydride.
2. The method for preparing a modified silica / polyimide separation membrane according to claim 1, characterized in that, In step (2), the ratio of the amount of graphene oxide-metal oxide precursor composite powder, diamine monomer, dianhydride monomer, and solvent is 1~8 g: 0.1~1 mol: 0.1~0.5 mol: 200~300 mL.
3. The method for preparing a modified silica / polyimide separation membrane according to claim 2, characterized in that, The reaction temperature in step (2) is 40~60 ℃; the reaction time is 4~8 h; the polycondensation reaction temperature is 20~30 ℃; and the polycondensation reaction time is 2~5 h.
4. The method for preparing a modified silica / polyimide separation membrane according to claim 3, characterized in that, The method for preparing the silica sol in step (3) is as follows: mix silicon source, anhydrous ethanol and water, and then add an acidic catalyst to react and obtain silica sol.
5. The method for preparing a modified silica / polyimide separation membrane according to claim 4, characterized in that, The volume ratio of the silica sol and the modified polyamic acid solution in step (3) is 1~5:3~10.
6. A method for preparing a modified silica / polyimide separation membrane according to claim 1 or 5, characterized in that, The calcination conditions in step (3) are as follows: first, heat the temperature to 200-250 ℃ at a rate of 0.5-2 ℃ / min and hold for 0.5-1.5 h, then heat the temperature to 350-450 ℃ at a rate of 1-5 ℃ / min and hold for 1-3 h.
7. A modified silica / polyimide separation membrane prepared by the method of any one of claims 1 to 6.
8. The application of the modified silica / polyimide separation membrane according to claim 7 in carbon dioxide separation.
Citation Information
Patent Citations
Three-dimensional structure TiO2-oxidized graphene nanocomposite in-situ polymerization doped polyimide film and preparation method thereof
CN106807255A